Utilization of a Porous Cu Interlayer for the Enhancement of Pb-Free Sn-3.0Ag-0.5Cu Solder Joint - Nashrah Hani Jamadon; Ai Wen Tan; Farazila Yusof; Tadashi Ariga; Yukio Miyashita; Mohd Hamdi (Metals, 2016)
The joining of lead-free Sn-3.0Ag-0.5Cu (SAC305) solder alloy to metal substrate with the addition of a porous Cu interlayer was investigated. Two types of porous Cu interlayers, namely 15 ppi—pore per inch (P15) and 25 ppi (P25) were sandwiched in between SAC305/Cu substrate. The soldering process was carried out at soldering time of 60, 180, and 300 s at three temperature levels of 267, 287, and 307 °C. The joint strength was evaluated by tensile testing. The highest strength for solder joints with addition of P25 and P15 porous Cu was 51 MPa (at 180 s and 307 °C) and 54 MPa (at 300 s and 307 °C ), respectively. The fractography of the solder joint was analyzed by optical microscope (OM) and scanning electron microscopy (SEM). The results showed that the propagation of fracture during tensile tests for solder with a porous Cu interlayer occurred in three regions: (i) SAC305/Cu interface; (ii) inside SAC305 solder alloy; and (iii) inside porous Cu. Energy dispersive X-ray spectroscopy (EDX) was used to identify intermetallic phases. Cu6Sn5 phase with scallop-liked morphology was observed at the interface of the SAC305/Cu substrate. In contrast, the scallop-liked intermetallic phase together with more uniform but a less defined scallop-liked phase was observed at the interface of porous Cu and solder alloy.